Rabies in medieval Persian literature – the Canon of Avicenna (980–1037 AD) - Dalfardi, Behnam (BioMed Central, 2014)
Ibn Sina (980–1037 AD), known by his full name Abu Ali al-Hussain ibn Abdallah ibn Sina and the Latin name ‘Avicenna’, was a Persian scholar who is primarily remembered for his contributions to the science of medicine. He authored Al-Qanun fi al-Tibb (The Canon of Medicine). Sections of his work are devoted to detailed descriptions of a number of infectious illnesses, particularly rabies. Avicenna described rabies in humans and animals and explained its clinical manifestations, route of transmission, and treatment methods. In this article, our goal is to discuss Avicenna’s 11(th)-century points of view on rabies and compare them with modern medical knowledge.